BIOCHEMICAL ANALYSIS OF VARIABLES IN A PROOF OF CANOEING (Fiep Bulletin - online, 2012)
Objective: The objective of this study was to analyze biochemical markers of athletic performance in the light of a clinical context and athletic. Methods: We collected peripheral blood samples (8 mL) of 15 paddlers at rest and 15 minutes after a race official. Then, there were blood count, analysis of biochemical markers, muscle damage and lipid profile. Results: Statistical analysis of results showed a significant increase (p
Keywords: Injuries; Canoeing; Chemical analysis of blood